WEAPONIZING COMMUNICATION. WORDS VS. BULLETS IN THE RUSSIAN-UKRAINIAN WAR - COJOCARU, Iulia-Alexandra (Strategic Impact, 2024)
In the light of the ongoing Russian-Ukrainian conflict, the article is built around the aim of contributing to a better understanding of the current information environment, as it is necessary both for the public opinion and for the authorities to adapt and respond effectively to the security environment dynamics. The present paper seeks response to the following research question: “How did the Ukrainian Strategic Communication (StratCom) campaigns function in supporting the Ukrainian state to resist the first year of war?”. For the development of the answer, we relied on a qualitative approach, analysing several discourses of the Ukrainian President in mass-media, in the first year of the war. We started from identifying some key-aspects regarding the background of the Russian-Ukrainian relations that Kremlin has exploited in developing their hostile information campaigns, such as common historical landmarks or the religious, cultural and linguistic values shared by these two states. Next, we observed how these issues were included in the Russian officials’ discourse through various messages. Further, we presented Ukraine’s information strategy, implemented beginning with 2014 (after Crimea’s annexation), that was mainly carried through their StratCom campaigns, so that in the final part of the article to analyse some elements of Ukraine’s President discourses, starting with the first days of the war. Our conclusions lead to the fact that Ukraine’s StratCom campaigns have decisively contributed to supporting its resistance in the first year of constant attacks from an undeniably stronger enemy.